Inward Rectifier K+ Currents Are Regulated by CaMKII in Endothelial Cells of Primarily Cultured Bovine Pulmonary Arteries. - Lihui Qu; Lei Yu; Yanli Wang; Xin Jin; Qianlong Zhang; Ping Lu; Xiufeng Yu; Weiwei Zhong; Xiaodong Zheng; Ningren Cui; Chun Jiang; Daling Zhu (PLoS ONE)
Endothelium lines the interior surface of vascular walls and regulates vascular tones. The endothelial cells sense and respond to chemical and mechanical stimuli in the circulation, and couple the stimulus signals to vascular smooth muscles, in which inward rectifier K+ currents (Kir) play an important role. Here we applied several complementary strategies to determine the Kir subunit in primarily cultured pulmonary arterial endothelial cells (PAECs) that was regulated by the Ca2+/calmodulin (CaM)-dependent protein kinase II (CaMKII). In whole-cell voltage clamp, the Kir currents were sensitive to micromolar concentrations of extracellular Ba2+. In excised inside-out patches, an inward rectifier K+ current was observed with single-channel conductance 32.43 ± 0.45 pS and Popen 0.27 ± 0.04, which were consistent with known unitary conductance of Kir 2.1. RT-PCR and western blot results showed that expression of Kir 2.1 was significantly stronger than that of other subtypes in PAECs. Pharmacological analysis of the Kir currents demonstrated that insensitivity to intracellular ATP, pinacidil, glibenclamide, pH, GDP-β-S and choleratoxin suggested that currents weren't determined by KATP, Kir2.3, Kir2.4 and Kir3.x. The currents were strongly suppressed by exposure to CaMKII inhibitor W-7 and KN-62. The expression of Kir2.1 was inhibited by knocking down CaMKII. Consistently, vasodilation was suppressed by Ba2+, W-7 and KN-62 in isolated and perfused pulmonary arterial rings. These results suggest that the PAECs express an inward rectifier K+ current that is carried dominantly by Kir2.1, and this K+ channel appears to be targeted by CaMKII-dependent intracellular signaling systems.